ANALISIS ALTMAN Z''-SCORE SEBAGAI ALAT EARLY WARNING SYSTEM RISIKO FINANCIAL DISTRESS STUDI KASUS PT WASKITA KARYA (PERSERO) TBK - Murviana Koto; Ikhsan Abdullah (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2026)
This study examines the level of financial distress risk at PT Waskita Karya (Persero) Tbk over the 2021–2024 period using the Altman Z''-Score model as an early warning system within the framework of financial risk management. The study is motivated by the persistent financial pressure faced by state-owned construction companies, characterized by high leverage, limited liquidity, and heavy reliance on long-term debt financing. Secondary data are obtained from audited consolidated financial statements and analyzed using a descriptive quantitative approach with a longitudinal case study design. The findings reveal that although the Z''-Score values demonstrate a gradual improving trend throughout the observation period, the company consistently remains within the distress zone, indicating a sustained and elevated risk of bankruptcy. These results confirm the effectiveness of the Altman Z''-Score model as an early warning tool for identifying financial risk and provide important implications for managerial decision-making and financial restructuring policies, particularly for highly leveraged construction firms operating in emerging markets.